Andrographolide Exerts Antihyperglycemic Effect through Strengthening Intestinal Barrier Function and Increasing Microbial Composition of Akkermansia muciniphila. (23rd July 2020) - Su, Hongming; Mo, Jianling; Ni, Jingdan; Ke, Huihui; Bao, Tao; Xie, Jiahong; Xu, Yang; Xie, Lianghua; Chen, Wei
Abstract : Accumulating evidence indicates that type 2 diabetes (T2D) is associated with intestinal barrier dysfunction and dysbiosis, implying the potential targets for T2D therapeutics. Andrographolide was reported to have several beneficial effects on diabetes and its associated complications. However, the protective role of andrographolide, as well as its underlying mechanism against T2D, remains elusive. Herein, we reported that andrographolide enhanced intestinal barrier integrity in LPS-induced Caco-2 cells as indicated by the improvement of cell monolayer barrier permeability and upregulation of tight junction protein expression. In addition, andrographolide alleviated LPS-induced oxidative stress by preventing ROS and superoxide anion radical overproduction and reversing glutathione depletion. In line with the in vitro results, andrographolide reduced metabolic endotoxemia and strengthened gut barrier integrity in db/db diabetic mice. We also found that andrographolide appeared to ameliorate glucose intolerance and insulin resistance and attenuated diabetes-associated redox disturbance and inflammation. Furthermore, our results indicated that andrographolide modified gut microbiota composition as indicated by elevated Bacteroidetes/Firmicutes ratio, enriched microbial species of Akkermansia muciniphila, and increased SCFAs level. Taken together, this study demonstrated that andrographolide exerted a glucose-lowering effect through strengthening intestinal barrier function and increasing the microbial species of A. muciniphila, which illuminates a plausible approach to prevent T2D by regulating gut barrier integrity and shaping intestinal microbiota composition.